Exploration of the needs and development of Arabic learning content based on Google Sites - Ilahi, Muhamad Muzaki Kurnia; Machmudah, Umi; Yurisa, Penny Respati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
In this digital era, the integration of technology in learning is very important. However, Al-Hikam Middle School in Jombang still do not maximize the use of technology in learning Arabic. The impact is that students are not able to achieve the learning targets that must be achieved because they often feel bored while learning. This research aims to explore the needs of teachers and students at Al-Hikam Middle School in Jombang to develop Arabic learning content based on Google Sites. This study uses a qualitative descriptive approach. Data were collected through interviews, observations and documentation. Triangulation is carried out to maintain the validity of the data. The results of this study show that teachers and students at Al-Hikam Middle School in Jombang need more interesting and interactive teaching materials because they still use printed modules. Based on the results of the needs analysis, a prototype of Arabic language learning content based on Google Sites was produced consisting of several types, including; vocabulary content, grammar, and four language skills (listening, speaking, reading, writing) which are presented in the form of text, animated images, audio, video and also equipped with interactive quizzes.' From this study, it is hoped that there will be further research to test its feasibility and effectiveness.